Gender and racial inequality in U.S. credit markets - Wentzel-Long, Melanie G., author; Bernasek, Alexandra, advisor; Pena, Anita, committee member; Pressman, Steven, committee member; Weiler, Stephan, committee member; Daum, Courtenay, committee member (Colorado State University. Libraries, 2019)
Outstanding household debt in the U.S. has grown dramatically since the 1980s, and households' borrowing activity is on track to return to levels unseen since the 2008 Financial Crisis. There has been limited research in economics on how patterns of credit use reflect and reproduce inequality by gender and race. In this study, I apply an intersectional feminist lens to household finance with four empirical investigations of women's position in credit markets. The papers are situated in an historically informed theoretical framework positing that women have been subject to three interconnected phenomena as consumers of credit: stigmatization, conditional inclusion, and exclusion. Chapter 2 investigates the relationship between borrowing from friends or family and financial exclusion, motivated by work in sociology suggesting that such informal borrowing has long-run costs and may be disproportionately used by women. I find that Black women are two to three times more likely than White respondents to plan on using informal borrowing as their primary coping strategy in the case of an emergency expense. Unobserved factors such as access to bank branches appear to link financial exclusion and informal borrowing. Chapter 3 explores differences by gender and race in U.S. high school students' aversion to borrowing for college and in the impacts of debt aversion. Female students and Black students are more likely to have a low but positive willingness to borrow for college than other groups. Moderate debt aversion is linked to lower levels of college enrollment, less borrowing, and lower costs of attendance, while strong debt aversion reduces the probability of enrolling in college for men only. Chapters 4 and 5 identify gendered and racialized trends in the growth of household debt surrounding the 2008 Financial Crisis. The results provide mixed evidence that high-cost mortgage lending targeted women or Black or Hispanic respondents. These groups experienced greater growth in consumer debt levels and debt burden relative to income than other groups post-crisis.
Keywords: credit; gender inequality; racial inequality; debt; 2008 Financial Crisis; household finance